ROMA HUKUKUNDA YARDIM NAFAKASI YÜKÜMLÜLÜĞÜ - (:unkn) unknown (My University, 2013)
Roma aile yapısındaki değişim sonucunda gerçekleşen yeniliklerden biri de nafaka yükümlülüğünün kabul edilmiş olmasıdır. Bu çalışmada Roma hukukunda klasik hukuk devrinde kabul edilmeye başlayan yardım nafakası yükümlülüğünün kapsamı ve şartları incelenmiştir.

Another innovation that took place as a result of the changes in the Roman family structure is that statutory duties to maintenance obligation have been accepted. In this study, the scope and conditions of this maintenance obligation, which started to get accepted in the classical law period of the Roman law, have been examined.
Keywords: Hukuk